Developing Efficient Thermophilic Cellulose Degrading Consortium for Glucose Production From Different Agro-Residues - Singh, Saurabh; Jaiswal, Durgesh Kumar; Sivakumar, Nallusamy; Verma, Jay Prakash (Frontiers in Energy Research, 2019)
In the present study, 11 cellulose degrading bacterial strains were isolated from water and soil samples of hot springs in the Chumathang village, Leh and Ladakh region, India. The isolated strains were identified as Bacillus subtilis, Bacillus aryabhattai, Bacillus stratosphericus, Bacillus altitudinis, and Brevibacterium frigoritolerans by biochemical and molecular approaches. All the strains were evaluated for the total cellulase, endoglucanase, exoglucanase, and β-glucosidase enzyme activities. On the basis of overall individual cellulose degrading enzyme activities, three strains were selected to develop consortium to enhance their cellulase enzyme activities. The potent cellulose degraders B. stratosphericus BHUJPV-H5, B. subtilis BHUJPV-H19, and B. subtilis BHUJPV-H12 were selected for the consortium development. The effect of cellulase activities of bacterial strains were evaluated ranged up to 6.06 and 0.72 mg ml−1 glucose by agro-residues of sugarcane bagasse and wheat straw, respectively, after 1 h of incubation. Total cellulase enzyme activity of consortia was recorded two times higher than the individual organisms. These strains can be used for enhancing bioethanol production from lignocellulosic biomass, which can consequently boost biofuel production industry.